Korelasi Antara Kompetensi Dan Kontribusi Universitas Terhadap Keterampilan Dan Kompetensi Alumni - Djamaris, Aurino R A (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
To detect the quality of the graduates produced is not enough just to see its output, which is only seen from the ability of mastery of knowledge, skills and formal attitudes embodied in the Achievement Index achieved. It should also be detected from its outcome that is how many college graduates absorbed in the job market. Level absorbed graduates in the job market, and entrepreneurship is an indicator of the success of universities in graduated students (output). The subjects of this research are alumni of Bakrie University, graduated in 2015. The variables of this research are: (1) absorption of alumni in the job market and entrepreneurship; (2) waiting time to obtain employment; (3) suitability of jobs entered; and (4) perceptions of graduates on hard skills and soft skills. Methods of data collection are done through survey techniques. Based on the research data, it turns out that the waiting periods of alumni to get jobs of Bakrie University students graduated in 2015 to get ether job or entrepreneur has a mean of waiting periods 2,24 months, the graduate absorption rate for their first job is 96%. Those who work received the income range of work of 1 million rupiahs up to 30 million rupiahs per month (on average 7 million rupiahs). The types of jobs that can accommodate most (80%) are as employees of multinationals, national private companies, government (civil servant), 10% percent continue studies, and 5% run businesses/entrepreneurs. The alumni state that between what is given in the lecture and what they meet in the world of work has a very close or close relationship and their level of education has been in accordance with their field of work. Competence of graduates at the time both graduates in the form of hard skills and soft skills is quite good, while the highest average value is for internet use skills and the lowest value is the ability to negotiate. The average of alumni perception toward university contribution on graduate competencies good. The highest average value of university’s contributions is the ability to communicate and work with people in different cultures and backgrounds and the lowest score is the provision of general knowledge. From the correlation analysis results, there is a strong correlation between university contributions toward the competence of graduates. There is a strong correlation between the contribution of universities with the competence of graduates in the field of knowledge about the discipline of Science, knowledge of non-discipline of Science, hard skills competence and soft skills as well as managerial competences.